PRODUCTION OF LOW DIGESTIBILITY CONTENT FLOUR - Salsabilla Qodrundnada, Riza
Diabetes is a condition that impairs the body’s ability to process blood sugar scoring above the limit allowed. In 2017, more than 10 Million people in Indonesia was estimated to be diagnosed with this disease. Beside the increase of blood glucose, diabetes highly risked to occur with unbalanced intake and energy release leading to inactive and unhealthy lifestyle. Low-calorie food consumption is one of the alternative solutions to prevent diabetes. To solve this issue, breakthrough innovation method needed to lower the digestibility content in flour. In this research, analysis will be conducted to study the effect of drying process toward of flour color and the effect of different concentration of solvents in heat moisture treatment (HMT) process towards of the digestibility factor of sweet potato flour. This study will be divided into 2 main steps. Milling as the first step order where sweet potato will be sorted and washed, then the chips will be dried and grinded into flour form. Flour with the lowest color change (?E) will continue onto the second phase which is HMT. In the second step order, flour will be soaked in citric acid with concentration variation of 0; 0,05; dan 0,2 M, followed by incubation and drying with temperature of 110? to obtain low digestion degree. Lastly, flour attained will be evaluated by several parameters: antioxidant activity, starch fraction, swelling power, and solubility. Based on the research, it is known that drying process significantly affect the flout color with ?E value for oven drying is 17,37 and sun drying is 16,01. Based on the result, it is known that increasing the concentration of citric acid resulted the lower digestibility of flour. The lowest digestible flour is the flour uses citric acir 0,2 M as a solvent with value 0f 15,67% RDS (rapid digestable starch), 10,52% SDS (slowly digestible starch), and 31,1% RS (resistant starch). In addition, increasing the citric acid concentration resulted in decrease value of swelling power amount 21-40%. However, increasing the concentration of citric acid has no significantly affect of the solubility and antioxidant activity of flour. Based on the mass balance calculation, the flouring process resulted in a yield of 72,53% (wflour/wdried sweet potato).